Health practices in relation to communicable disease prevention and control in Bangui, Ilocos Norte, and their implications to health education - Malapit, Imelda Delgado 1931- (s.n.], 1972)
Health practices of the people of Bangui, Ilocos Norte were studied, relative to communicable disease prevention and control and the implications of the practices to health education.